KONTRIBUSI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU TAMAN KANAK-KANAK NEGERI MAMMINASAE LABESSI KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - U., Rosmini; Aminah, Sitti; Syamsiar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The principal’s contribituon in improving teacher performance, especially teachers at Mamminasae State Kindergarten, is one of the principal’s efforts to improve teacher performance in the learning process. This study aims to analyze, review and describe the principal’s controbution. This research method uses a descriptive approach. Data collection techniques include observation, interviews and documentation. The subjects of this research are school supervisor, teachers, sv\chool committees and community leaders. The result of the study show: 1) The proncipal’s contribution in improving the performance of teacher at Mamminasae Labessi State Kindergarten , Marioriwawo District, Soppeng Regency was carried out well through coacingand developing teachers’ abilities in the learning process, providing motivation by creating a conducive learning situation, providing opportunities for teachers to continue their education, placing them according to their fields and providing awards and fulfilling the needs for facilities and infrastructure. 2) Supporting factors include role models , supervision, training, motivation, and provision of facilities and infrastucture, while the obstacles include a lack of training funds, teachers lacking discipline/motivation , high administrative burdens, teachers living far away, inadequate school fecilities, and low community participation.